Implementation of Sharia Principles in Managing Halal Certified MSME Business - Author, Muhammad Nailul (Iqtishodia: Jurnal Ekonomi Syariah, 2024)
The rapid growth of the halal industry in Indonesia has heightened the importance of Sharia compliance in business management, particularly among micro, small, and medium enterprises (MSMEs) in Malang. This study aims to explore the extent of Sharia principles implementation in halal-certified MSMEs and the challenges they face in aligning their operations with Islamic guidelines. Utilizing a qualitative approach, in-depth interviews and observations were conducted with MSME owners to gain insights into their experiences. The results indicate that while many MSMEs actively implement Sharia principles in areas such as sourcing halal materials and ethical marketing, they encounter significant challenges, including limited access to certified suppliers and a lack of understanding of halal regulations. Furthermore, the study reveals that adherence to Sharia compliance enhances customer loyalty and trust, thereby improving business performance. This research contributes to bridging the gap between theory and practice in Sharia-compliant business management and provides practical recommendations for MSMEs to optimize their operations within the halal framework.